ASSESSMENT OF THE QUALITY OF OUTPATIENT PRESCRIPTIONS FROM VARIOUS CLINICAL SETTING IN A TERTIARY HOSPITAL, SAUDI ARABIA - ALSHAHRANI, SULTAN M. (International Journal of Applied Pharmaceutics, 2019)
Objective: The quality of prescribing influences, to a large extent, the health outcomes of patients as errors made could result in adverse drug reactions. The aim of this study is to assess determine the quality of outpatient prescriptions in various clinical settings in Aseer region, Kingdom of Saudi Arabia. Methods: An observational, cross-sectional descriptive study was carried out in various community pharmacies where the prescriptions received were analyzed for their quality. Results: The prescriptions were checked for the completeness of the patients’ biodata (name, age, sex, and hospital number), categories of drugs, prescribing by generic name, legibility of prescriber’s writing, the name, and signature of the prescriber. Two hundred and fifty prescriptions were collected and used for analysis. A significant number of the prescriptions were written in illegible (26%) handwriting. The name (15%), age (48%), and sex (46%) of the patient were not mentioned in the majority of the prescriptions. Most of the prescriptions (94%) failed to demonstrate the presence of address, height, and weight of the patient. Brand name of the drugs was mentioned in all the prescriptions, with only 17% of them having the generic name. The doctor’s name, signature was present in 81% and 70% of the prescription, respectively. Conclusion: Study shows that there is a need for improvement in the quality of prescription written by doctors. The adoption of a computer-aided prescribing system in an outpatient setting would go a long way in achieving this objective.